Prevalence of Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae in Ethiopia: A Systematic Review and Meta-Analysis - Teklehaimanot Kiros; Lema Workineh; Tegenaw Tiruneh; Tahir Eyayu; Shewaneh Damtie; Debaka Belete (International Journal of Microbiology)
Background. Antimicrobial resistance especially caused by extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE) has become a global public health concern. Globally, these isolates have remained the most important causes of several infections and associated mortality. Their rapid spread in Ethiopia is associated with a lack of regular surveillance and antibiotic stewardship programs. Isolates of ESBL-PE from different regions of Ethiopia were searched exhaustively. However, published data regarding the pooled estimate of ESBL-PE are not conducted in Ethiopia. For this reason, we systematically reviewed laboratory-based studies to summarize the overall pooled prevalence of the isolates recovered from various human specimens. Methods. An exhaustive literature search was carried out using the major electronic databases including PubMed, Web of Science, MEDLINE, EMBASE, CINAHL, Google Scholar, Cochrane Library, Scopus, and Wiley Online Library to identify potentially relevant studies without date restriction. Original articles which address the research question were identified, screened, and included using the PRISMA follow diagram. Data extraction form was prepared in Microsoft Excel, and data quality was assessed by using 9-point Joanna Briggs Institute critical appraisal tools. Then, data were exported to STATA 16.0 software for analyses of pooled estimation of outcome measures. Estimation of outcome measures at 95% confidence interval was performed using Der-Simonian-Laird’s random-effects model. Finally, results were presented via text, figures, and tables. Results. A comprehensive electronic database literature search has yielded a total of 86 articles. Among the total, 68 original articles were excluded after the review process. A total of 18 studies with 1191 bacterial isolates recovered from 7919 various clinical samples sizes were included for systematic review and meta-analysis. In this study, the pooled prevalence of ESBL-PE was 18% (95% CI: 9–26). Nine out of the total (50%) reviewed articles were studied using the combination disk test. Likewise, E. coli and K. pneumoniae (50% both) were the predominant isolates of ESBL-PE in addition to other isolates such as Salmonella spp. and Shigella spp. Conclusion. This meta-analysis has shown a low pooled estimate of ESBL-PE in Ethiopia.